2020
DOI: 10.1128/aac.01100-20
|View full text |Cite
|
Sign up to set email alerts
|

Resistance against Membrane-Inserting MmpL3 Inhibitor through Upregulation of MmpL5 in Mycobacterium tuberculosis

Abstract: Spiroketal indolyl Mannich bases (SIMBs) present a novel class of membrane-inserting antimycobacterials with efficacy in a tuberculosis mouse model. SIMBs exert their antibacterial activity by two mechanisms. The indolyl Mannich base scaffold causes permeabilization of bacteria and the spiroketal moiety contributes to inhibition of the mycolic acid transporter MmpL3. Here, we show that low-level resistance to SIMBs arises by mutations in the transcriptional repressor MmpR5 resulting in upregulation of the effl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several reports have described the in vitro isolation of mmpR5 mutants resistant to bedaquiline (BDQ) and clofazimine (CFZ) ( 39 , 40 ), mediated through increased MmpL5 efflux pump expression ( 40 ) and mmpR5 clinical mutants including from BDQ and CFZ naïve patients in both drug-sensitive and MDR-TB strain backgrounds ( 40 42 ). In addition, Li and colleagues demonstrated that mmpR5 mutants are resistant to the SIMBL class of MmpL3 inhibitors ( 43 ), suggesting that some MmpL3 inhibitors may be susceptible to efflux by MmpL5. To determine if mmpR5 mutations confer resistance to our inhibitors, we tested analogs against an mmpR5 mutant ( mmpR5 E21K ) isolated against an experimental compound HC2194.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have described the in vitro isolation of mmpR5 mutants resistant to bedaquiline (BDQ) and clofazimine (CFZ) ( 39 , 40 ), mediated through increased MmpL5 efflux pump expression ( 40 ) and mmpR5 clinical mutants including from BDQ and CFZ naïve patients in both drug-sensitive and MDR-TB strain backgrounds ( 40 42 ). In addition, Li and colleagues demonstrated that mmpR5 mutants are resistant to the SIMBL class of MmpL3 inhibitors ( 43 ), suggesting that some MmpL3 inhibitors may be susceptible to efflux by MmpL5. To determine if mmpR5 mutations confer resistance to our inhibitors, we tested analogs against an mmpR5 mutant ( mmpR5 E21K ) isolated against an experimental compound HC2194.…”
Section: Resultsmentioning
confidence: 99%